Queen's Royal College, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Exterior view of the Queen’s Royal College, situated at the corner of St Clair Avenue and Maraval Road in Port of Spain, Trinidad. This is a secondary school that admits male students only. Postcard number 08 56653.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; 1908; Schools--Trinidad and Tobago; High schools--Trinidad and Tobago; Public schools--Trinidad and Tobago; Education, Secondary--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Fences--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)